2006
DOI: 10.1111/j.1525-1470.2006.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Infection with Mycobacterium abscessus in a Child

Abstract: Nontuberculous mycobacteria can cause cutaneous infections in both children and adults. Localized nontuberculous mycobacterial infections of the skin have been reported in children following injections or surgical procedures. We report a child who developed a cutaneous nontuberculous mycobacterial infection after exposure of a skin wound to pond water. Cutaneous infection with the rapidly growing mycobacteria Mycobacterium abscessus was demonstrated by clinical and histologic evaluation on the lower leg of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…However, recently, infections in immunocompetent persons have been reported more frequently. These cases are soft-tissue infections associated with trauma and injection and epidemics or pseudoepidemics that have occurred in hospitals (6,12). Ninety-five percent of soft-tissue RGM infections are caused by members of the M. chelonae complex (7), which comprises M. chelonae, M. abscessus, and M. immunogenum.…”
mentioning
confidence: 99%
“…However, recently, infections in immunocompetent persons have been reported more frequently. These cases are soft-tissue infections associated with trauma and injection and epidemics or pseudoepidemics that have occurred in hospitals (6,12). Ninety-five percent of soft-tissue RGM infections are caused by members of the M. chelonae complex (7), which comprises M. chelonae, M. abscessus, and M. immunogenum.…”
mentioning
confidence: 99%
“…To our knowledge, this is only the second description of an outbreak of skin infections by M. abscessus in a population of immunocompetent children due to nontraumatic transmission. Brantley et al reported a skin infection by M. abscessus in a child, most likely subsequent to exposure of a wound to pond water. Two other outbreaks including children were described after injections of contaminated drugs (penicillin and lidocaine) .…”
Section: Discussionmentioning
confidence: 99%
“…Hier sind z. B. Aufenthalt in Teichwasser [1], in einem Planschbecken [2], in Whirlpools [10,20,39], aber auch in öffentlichen Bädern [4] sowie Verletzungen im Wasser [12,40] bzw. durch Kontakt mit Fischen bzw.…”
Section: Epidemiologieunclassified
“…Als Subspezies von M. chelonae zählt auch M. abscessus zu diesem Komplex [1][2][3][4][5][6]. Weniger oft wurden M. avium-intracellulare [7][8][9][10], M. gordonae [11][12][13][14][15], M. haemophilum [16][17][18][19], M. intermedium [20], M. kansasii [21][22][23], M. malmoense [24][25][26][27], M. scrofulaceum [28,29], M. simiae [30], M. flavescens [31] und M. peregrinum [28] bei diesen Patienten nachgewiesen (auf M. ulcerans wird hier nicht eingegangen).…”
unclassified